The rural to urban transition in developing countries : urbanisation and peri-urban land markets - Varkey, Amrutha Mary (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Increasing urbanisation and industrial development are occurring at the expense of shrinking forest cover and agricultural land in South Asia. Various land uses compete with each other, thus reducing forests and farmlands. This book addresses urbanisation and peri-urban land markets, with a special focus on Bangalore, one of the fastest growing cities in South Asia. It contributes to historic perspectives on the spatial transformation of peri-urban locales, as well as providing much-needed empirical evidence. The book discusses issues related to the context of peri-urban land use, land transactions, demand supply relationships and land prices in the peri-urban land market. The steep rise in land prices of the periphery, rapid changes in the land use pattern, active land transactions, growth of the real estate market and the challenge to implement efficient land use regulations are explored with the help of field evidence. Insights and challenges to land administration addressed in this book are common to other metropolitan cities, and the key message is that a separate peri-urban land policy is required for the major metropolitan cities of India and other developing countries. The book contributes to the understanding of how these spatial markets function in order to work towards an improved implementation of land policy in the context of dynamic rural-urban periphery. As such, it will appeal to researchers, scholars and students of regional, urban and agricultural economics, economic geography, urban and regional planning and environmental science. It will also be of great interest to city planners and policy makers, action-based think tanks focused on urban governance"--
Keywords: Urbanization -- India -- Bangalore; Rural-urban migration -- India -- Bangalore; Land use -- India -- Bangalore; BUSINESS & ECONOMICS / Urban & Regional; BUSINESS & ECONOMICS / Development / General